Leo Suryadinata (comp.), Chinese Adaptation and Diversity. Essays on Society and Literature in Indonesia, Malaysia & Singapore, Singapur, Center for Advanced Studies, Singapore University Press, 1993, X + 212 pp. - Cornejo Bustamante, Romer (Estudios de Asia y África, 1995)
Leo Suryadinata (comp.), Chinese Adaptation and Diversity. Essays on Society and Literature in Indonesia, Malaysia & Singapore, Singapur, Center for Advanced Studies, Singapore University Press, 1993, X + 212 pp.